Recomendações médico/a-paciente em consultas de aconselhamento genético e o processo de tomada de decisão - Böhm, Daiane Baldasso (Universidade do Vale do Rio dos Sinos, 2018)
Patients have the right to choose the most suitable among the different alternatives of health treatment (TOERIN et al., 2011), and thus need to be informed about the choices of possible treatments as well as of more specialized diagnostic exams so that they can reach the necessary autonomy to make a decision. (LANDMARK; GULBRANDSEN; SVENNEVIG, 2015; WESSELS; KOOLE; PENN, 2014). For this reason, professionals are supposed to provide patients with the necessary and existing information about the possible next step with some degree of neutrality, recognizing patients’ autonomy and knowledge. (LANDMARK; GULBRANDSEN; SVENNEVIG, 2014; DREW; HERITAGE, 1992). Non-neutral (biased) recommendations for a specific treatment or medical exam might represent an explicit stance of the professional’s deontic authority. (STEVANOVIC; PERÄKYLA, 2012). There is a lack of health interactional studies with naturalistic interactions i.e., “[…] data from daily situations which happen (and would happen) with or without the researcher presence” (OSTERMANN; MENEGHEL, 2012, p. 14, our translation) in Brazilian Portuguese language that observe physician-patient recommendations and the decision-making process. We highlight, however, that developing a research concerning this theme, a whole professional class must be beneficiated from the results. This kind of analysis may contribute for the formation of professionals who work in areas in which recommending/making decisions is current practise. The present master’s dissertation analyzes how the medical-pregnant patients’s (medium and high risk pregnancies) recommendation sequence is done in Genetic Counselling (GC) consultations. Along the consultations, a geneticist recommends the foetal-genetic test involving procedures (i.e. amniocentesis or cordocentesis) for further foetal karyotype analysis. Both procedures are invasive and not free risk. This study consists of (1) identifying the Overall Structural Organization (OSO) of the segments in which there are recommendations (macro structural level of interactional analysis); (2) describing the recommendation phases in the analysed consultations; (3) analysing the linguistic-interactional features of recommendation sequences (micro structural level of analysis); (4) investigating, from a conversation analytical perspective (SACKS, 1992), how (and if) the professional deontic authority takes shape in these sequences, and its relation with the participants epistemic domain. In order to do so, the data analysis was done under Conversation Analysis (CA) theoretical-methodological approach (SACKS; SCHEGLOFF; JEFFERSON, 1974; CLIFT, 2016), which enables a meticulous analysis and turns of talk retrospective that make interactional sequences. The research context is a public hospital in the south of Brazil, which offers GC consultations for pregnant patients with medium and high risk pregnancies. This study consists of a subproject of a larger project coordinated by Profa. Ana Cristina Ostermann, named A mobilização do saber e do fazer: episteme e deonticidade na fala-em-interação institucional e na conversa cotidiana, as the analysed interactions also come from the same project.
Keywords: Recomendações médico/a-paciente; Tomada de decisão; Domínio deôntico e Domínio epistêmico; Fala-em-interação; Aconselhamento genético; Physician-patient recommendations; Decision making; Deontic and epistemic domains; Talk-in-interaction; Genetic counselling; ACCNPQ::Lingüística, Letras e Artes::Lingüística